IMPLEMENTASI LOGIKA FUZZY PADA SISTEM MONITORING ONLINE SUHU SAPI POTONG BERBASIS IOT - Tresna Utama, Abi; Panji Sasmito, Agung; Faisol, Ahmad (JATI (Jurnal Mahasiswa Teknik Informatika), 2021)
Cows are one of the leading commodities in several regions in Indonesia, one of which is Lampung province. From the census data, the population of cattle breeders has resulted in an increase every year. With the understanding of livestock farmers in cultivating beef cattle is still manual, and does not pay attention to the temperature conditions in the cow and around the cow so that it has an impact on reducing the weight of the cow. For this reason, a system is made to monitor cow temperature and environmental temperature in order to facilitate livestock managers in dealing with problems related to cow temperature. In this study, the website-based Inter of Things is implemented using the fuzzy mamdani logic method which is used to determine how long the mini water pump has been running. With this system, livestock managers are expected to be able to monitor environmental temperature and cow temperature, and to keep the cow temperature stable. The hardware used is an Arduino Uno which acts as a controller. System testing is carried out using the MLX90614 sensor to detect cow's body temperature, the DHT11 sensor to detect environmental temperature and humidity, the HC-SR04 sensor to measure water level. The results obtained from testing the MLX90614 sensor at a distance of 3 cm have an average error of 4.2% and an average difference of 1.6 ° C, at a distance of 5cm have an average error of 4.3% and an average difference of 1.7. ° C, at a distance of 10 cm has an average error of 5.2% and an average difference of 2.0 ° C, at a distance of 20 cm it produces an average error of 9.6% and an average difference of 3.6 ° C . DHT11 sensor testing resulted in an average error of 2.4% and an average difference of 0.7 ° C. testing the HC-SR04 sensor resulted in an average error of 5.53% and an average difference of 0.3.